2002
DOI: 10.1115/1.1505849
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nonuniform Inlet Conditions on Endwall Secondary Flows

Abstract: Exit combustor flow and thermal fields entering downstream stator vane passages in a gas turbine engine are highly nonuniform. These flow and thermal fields can significantly affect the development of the secondary flows in the turbine passages contributing to high platform heat transfer and large aerodynamic losses. The flow and thermal fields combine to give nonuniform total pressure profiles entering the turbine passage which, along with the airfoil geometry, dictate the secondary flow field. This paper pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Hartland et al [17]. and Chyu [18] on controlling the secondary flows using concepts such as end wall contouring; and the work by Hermanson and Thole [19] on the effects of nonuniform inlet flow conditions on secondary flows.…”
Section: Review Of Past Literaturementioning
confidence: 98%
“…Hartland et al [17]. and Chyu [18] on controlling the secondary flows using concepts such as end wall contouring; and the work by Hermanson and Thole [19] on the effects of nonuniform inlet flow conditions on secondary flows.…”
Section: Review Of Past Literaturementioning
confidence: 98%
“…The results of an experimental campaign carried out in a large-scale low speed axial turbine presented by (Butler, et al, 1989) demonstrated the increase of secondary flows due to temperature gradients originating from temperature distortions propagating from the turbine inlet. The influence of realistic turbine nonuniform inlet conditions on secondary flows was investigated also analytically (Lakshminarayana, 1975) and computationally by (Hermanson & Thole, 2002), who highlighted the need to consider realistic stage inlet profiles, due to the influence of pressure and temperature gradients on the secondary flows intensity.…”
Section: Introductionmentioning
confidence: 99%
“…That effect was attributed to the increase in the secondary flow due to temperature gradients. The impact on vorticity production due to temperature non-uniformities was early investigated analytically by Lakshminarayana 12 and later computationally by Hermanson and Thole 13 who showed that zero streamwise vorticity is produced through a turbine stator blade passage when stagnation temperature distortion is not accompanied by gradients in Mach number and stagnation pressure. The results of Hermanson and Thole demonstrated the need to consider more realistic turbine inlet profiles in the simulations due to the effect of pressure gradient on the magnitude of secondary flows.…”
Section: Introductionmentioning
confidence: 99%